Revenge Tragedy In Eka Kurniawan’s Novel Cantik Itu Luka - Lubis, Riski Safitri (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
This novel talks about a beautiful woman who is forced into prostitution at the end of the colonial period. She bears three daughters – all are beautiful and cause much strife so that when she becomes pregnant again, she prays for an ugly child. Her prayer is answered. The story follows the lives of her daughters and their children so the scope of this family story is wide. It is a fascinating story. On the other hand, it can be a curse not only to themselves but also to others as the characters in the novel. But there is more phenomenon found in the novel such as magic realism, superstition and the brutal daily lives of many people.